Mental Pain Surrounding Suicidal Behaviour: A Review of What Has Been Described and Clinical Recommendations for Help - Morales, Susana; Barros, Jorge (Frontiers in Psychiatry, 2022)
Objective: To conduct a comprehensive review of scientific publications related to mental pain and suicide risk in order to deepen relevant aspects to guide clinical interventions. Method: Using a text analysis tool, we collected the terms most frequently linked with that situation in published results of research using various tools to evaluate mental pain or psychache. Discussion: We propose clinical interventions for the clinical conditions most commonly associated with mental pain.